Sexual Perfomance of White Karaman and Kivircik Rams Exposed to Fat-Tailed Ewes - Bozkurt, Tanzer (Medwell Online, 2012)
This study was conducted to evaluate the sexual performance of White Karaman and Kivircik rams of different breed groups. About 16 ram each of White Karaman and Kivircik breed were subjected to sexual performance tests by being exposed to oestrous White Karaman ewes for 30 min period. Anogenital sniffing Flehmen response, nudging and following ewes features of rams were assement at breed groups. Results of the present study indicate that White Karaman are more capable of mating with fat-tailed ewes than the Kivircik rams.
Keywords: Ram; sexual behaviour; fat-tailed ewe; White Karaman; Kivircik; Turkey